Lack of care? Women's experiences of maternity bladder management. (2nd January 2019) - Gutiérrez, Verónica Blanco; Fader, Mandy; Monga, Ash; Kitson-Reynolds, Ellen
Abstract : Background: A healthy urinary system is vital to every woman's life, and the relationship between childbirth and bladder dysfunction has been well documented in the medical literature. Aims: To explore women's bladder care experiences during the antepartum, intrapartum, and postpartum periods. Methods: An exploratory, descriptive research study with nine in-depth semi-structured interviews. Findings: Thematic analysis showed three themes: 'muddling through to earn "a badge of honour"', 'caring for a baby, but who cares for me?' and 'do you speak bladder language?' with an overarching theme of 'lack of bladder care'. Women's experiences reflected a lack of understanding, information, and promotion regarding bladder care, aggravated by the use of ambiguous language when professionals communicated with women about bladder health. Conclusions: Bladder care was very limited for women during the antepartum, intrapartum and postpartum period although reports of urinary incontinence were frequent. Bladder care could therefore be characterised as 'lack of bladder care'. Clinicians should become more proactive in delivering information and promoting bladder health during these periods but that attention needs to be paid to communication methods.